Digital PR Strategy and Institutional Image in Islamic Boarding Schools - Irfan Maulana; Nino Nopriandi Saleh; Puput Aryanto; Roisatul Agitsah Hilwana Putri; Andini Meifiana (Jambura Science of Management, 2026)
Purpose: The purpose of this research is to examine how digital communication strategies and social media credibility shape institutional image, trust, and public involvement, and to recommend effective digital public relations practices.Design/Methodology/Approach: Employing a mixed methods sequential exploratory design, the study began with qualitative thematic analysis of interviews with key stakeholders, followed by quantitative testing using Structural Equation Modelling (SEM) with 215 respondents.Findings: Six major themes were revealed: strategic digital communication, stakeholder engagement, governance and management, values and positioning, issues and crises, and impacts and outcomes. SEM results indicate that social media credibility significantly influences institutional image and public engagement. Institutional image mediates the relationship between credibility and engagement. However, digital communication strategies alone do not significantly affect public engagement unless governance, clear procedures, and competent human resources support them.